Effect of binder concentration on ternary MnO2/CuS/reduced graphene oxide material for supercapacitor applications - Chaudhary, Manika; Oyelola, Lekan; Glidden, Thomas; Broadbridge, C.; LeMaire, Peter; Sharma, Rakesh; Singh, Vinamrita; Sahi, Vikhyat; Singhal, Rahúl (Journal of Solid State Electrochemistry, 2025)
Keywords: Capacitance; Chemical engineering; Chemistry; Electrochemistry; Electrode; Energy storage; Graphene; Inorganic chemistry; Materials science; Metallurgy; Nanotechnology; Oxide; Physical chemistry; Supercapacitor; Synthesis; Ternary operation; Thermodynamics; X-ray diffraction; dept.phy

Effect of reduce graphene oxide (Rgo) on electrochemical performance of Cus for supercapacitor applications - Singhal, Rahul; Thorne, David; Chaudhary, Manika; Bhardwaj, Shiva; Abazi, Rilind; Gupta, Ram K.; Scanley, Jules; Broadbridge, Christine C.; Singh, B. P.; LeMaire, Peter K.; Sharma, Rakesh K. (2023)
CuS and CuS-rGO nanocomposites were synthesized by the hydrothermal method. The synthesized CuS and rGO-CuS nanocomposite materials were physically characterized by X-ray diffraction (XRD) and scanning electron microscope (SEM) and were evaluated electrochemically for supercapacitor applications. The specific capacitance of CuS was determined to be 207 F/g, 150 F/g, and 97 F/g at a current density of 0.5 A/g, 5 A/g, and 20 A/g, respectively. The rGO-CuS nanocomposite showed improved specific capacitance of 350 F/g, 251 F/g, and 149 F/g at a current density of 0.5 A/g, 5 A/g, and 20 A/g, respectively.
Keywords: CuS; SEM; Supercapacitors; dept.phy; rGO; specific capacitance